Prevalance of Essential Hypertension in School Going Early and Mid Adolescent Children of Kathmandu Valley - Kafle, Raju; Shrestha, Srijana (Journal of Universal College of Medical Sciences, 2013)
OBJECTIVE: The general objective of the study is to find out prevalence of essential hypertension among early and mid adolescent of school going children of Kathmandu valley. The specific objective of the study is to identify various risk factors (eg diet, family history, obesity) and its correlation with childhood Hypertension and to study the correlation of childhood hypertension with BMI. METHODS : It is a School based cross sectional study done in schools of kathmandu valley. School going children aged 10yrs to 16 years from four different schools of Kathmandu and lalitpur were taken as study population. Three were private schools and one was government school. All school going children aged 10- 16years were included in the study. Children with any chronic illnesses, were excluded from the study. RESULTS: A total of 613 students were included between the age group of 10 years- 16 years amongst which 326(53.2%) were male and 287(46.8%) were female. Of these 426(69.5%) were in early adolescent age (10-13 yrs) and 187(30.5%) in mid adolescent age(14-16 yrs)..At the end of three screenings 27 cases(4.40%) had abnormal blood pressure. Among these 17 (2.8%) cases had high systolic blood pressure and 21(3.4%) had high diastolic blood pressure of different stages. DOI: http://dx.doi.org/10.3126/jucms.v1i2.8406 Journal of Universal College of Medical Sciences Vol.1(2) 2013: 24-29